Pengaruh Terapi ARV untuk Meningkatkan Kualitas Hidup Pasien HIV/AIDS: A Literature Review - Siska Mutiara Hikmah S; Hasri Kuswiharyanti; Vidi Ahmad Raafi; Ninik Juarti; Tria Amaliadiana (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
INTRODUCTION : Acquired immunodeficiency syndrome (AIDS) is a collection of disease symptoms that attack human body after HIV (Human Immunodeficiency Virus) damage the immune system. HIV-AIDS is a disease that cannot be cured now, but there are therapies to help improve the quality of life for people with HIV, and also to increase the antibodies for people with HIV and the therapy is called ARV. The main goal of ARV treatment is to reduce the number of HIV viruses to delay and stop the growth of the virus. METHOD : Determine the latest intervention regarding evidence based on HIV-AIDS and ARV pharmacological therapy. After determining the topic, the next step is to search for literatures that will be reviewed, the literatures are in the form of scientific journals obtained from databases such as: Science Direct, ProQuest, and Google Scholar with keyword: “ARV for HIV/AIDS” for international journals and for the national journals using Google search engine from 2014-2019. RESULT : Based on journals as a literature, the conclusion is that ARV therapy can improve the quality of life for people with HIV-AIDS, the characteristic of the therapy is to form the antibodies and produce proinflamation agents to reduce the growth of the viruses, beside that the therapy is also effective if it given directly to HIV-AIDS patients who early diagnosed as a HIV-AIDS patient, and also the ARV therapy can improve the quality life of children and reduce the risk of HIV-AIDS in children who have mothers with HIV-AIDS. CONCLUSION : ARV therapy can improve the quality of life and prevent the transmission from mothers with HIV to their children.